Pengembangan Media Pembelajaran Museum Virtual pada Mata Pelajaran Sejarah Kelas X SMA - Alhamdani, Ega; Novrianti, Novrianti; Syafril, Syafril; Anugrah, Septriyan (AHKAM, 2023)
The problem with this development for history subjects are not fully understood by students. This is characterized by the materials and media used not contributing to maximum learning. Only textbooks are used as teaching materials, and the media used by the teacher is in the form of his PPT, but the PPT media does not achieve the learning objectives. The use of PPT media has disadvantages in the form of lack of attractiveness of the materials, students are easily bored and do not study seriously. Also, lack of interest in the material leads to lack of enthusiasm in these students. A decline in student learning outcomes. This development study aims to create a valid, practical and effective history class X SMA virtual media learning museum. Media verification sheets, material verification sheets, student response questionnaires, and effectiveness questions serve as tools. The results of the needs analysis, i.e. the learning materials taught are not fully understood by the students and the materials and media used are given the greatest possible consideration when studying in the test subjects of high school student Adabiah 2 Padang in class X. It wasn't. The results of this study show a media validation result of 4.9 (98%) on a very valid basis. The material validation result is 4.9 which is a very valid criterion. Student Evaluation Results 4.75. The validity result obtained is t-count is 18.28 and t-table is 2.060, so the result is t-count > t-table. From this, we can conclude that there is a significant difference in learning outcomes before and after the use of virtual museum media for history class X subjects.